Answer:
(x + 4)^2 + 3 = 0
Explanation:
When you multiply out (a + b)^2, you get a^2 + 2ab + b^2. We already know the a^2 term, which is x^2. We can deduct the first term of the square is x because x * x is x^2, and x would correspond with a. Next, we can connect the 2ab term with 8x, as it includes the variable x.
2ab = 8x
We have established a = x, so:
2xb = 8x
b = 4
We can put this together to get the square:
(x^2 + 8x + 16) + 3 = 0
(the three is added to get a last term of 19 in the given equation)
When we factor the square, it turns out as:
(x + 4)^2 + 3 = 0
Note: Sorry if the answer was a bit confusing, this is kinda hard to explain.